Structure-function relationships of human apolipoprotein A-I: Role of the amino-terminal amphipathic alpha-helices. - Scott, Brian R. (University of Ottawa (Canada), 2002)
To investigate the role(s) of the globular domain (residues 1-43) and the first class A helix (residues 44-65) of apolipoprotein A-I (apoA-I) in the metabolism of high density lipoproteins (HDL), we have taken a combined in vitro and in vivo approach. This work demonstrates that both the globular domain and helix 1 of apoA-I are important for the maturation of HDL. Deletions of these domains were associated with progressive impairments in the ability of apoA-I to activate lecithin:cholesterol acyltransferase (LCAT) and form cholesterol ester rich HDL. While phospholipid binding was significantly reduced for both apoA-I mutants relative to wild-type apoA-I, cholesterol efflux was not affected by these deletions. We propose both the globular domain and helix 1 are critical LCAT activating domains of apoA-I and are required for the maturation of HDL in vivo.
Keywords: Chemistry, Biochemistry.